Recent progress, mechanisms, and perspectives for crystal and interface chemistry applying to the Zn metal anodes in aqueous zinc‐ion batteries. Issue 2 (28th March 2022) - Zhang, Zhengchunyu; Xi, Baojuan; Ma, Xiaojian; Chen, Weihua; Feng, Jinkui; Xiong, Shenglin
Abstract: The need for large‐scale electrochemical energy storage devices in the future has spawned several new breeds of batteries in which aqueous zinc ion batteries (AZIBs) have attracted great attention due to their high safety, low cost, and excellent electrochemical performance. In the current research, the dendrite and corrosion caused by aqueous electrolytes are the main problems being studied. However, the research on the zinc metal anode is still in its infancy. We think it really needs to provide clear guidelines about how to reasonably configure the system of AZIBs to realize high‐energy density and long cycle life. Therefore, it is worth analyzing the works on the zinc anode, and several strategies are proposed to improve the stability and cycle life of the battery in recent years. Based on the crystal chemistry and interface chemistry, this review reveals the key factors and essential causes that inhibit dendrite growth and side reactions and puts forward the potential prospects for future work in this direction. It is foreseeable that guiding the construction of AZIBs with high‐energy density and long cycle life in various systems would be quite possible by following this overview as a roadmap. Abstract : Based on the crystal chemistry and interface chemistry, we organize this review to look back and put forward the design around the substrate, electrolyte, and their interface. These key points mainly pay close attention to inhibit dendritic growth and side reactions, then present the potential prospects for future work in this direction. It is foreseeable that this overview as a roadmap could realize accurate control of homogeneous Zn deposition and guide the construction of zinc batteries with high performance and reversibility.